Metaphysics and the Existential Problematic of Human Finitude - Nutter, Taylor (Lumen et Vita, 2017)
Rather than being of little practical importance, the metaphysical underpinnings of a given horizon determine the character of its existential problematic. With the breakdown of classical metaphysics concomitant with the modern turn to the subjective, the existential problematic of finitude as ultimate horizon arose. According to this subjective turn, the human person can no longer engage the world as though it were in itself constituted by transcendently grounded meaning and value. Standing within this genealogical lineage, Martin Heidegger undertook a phenomenological investigation into the existential constitution of the human person which defines authenticity in terms of finitude. For the early Heidegger, human life is essentially ‘guilty’. This guilt, however, is not the traditional cognizance of one’s sinfulness, but the foundational Nichtigkeit (‘nullity’) of life and its attendant possibilities in the light of the ultimate finality of death. Authenticity, then, consists of a resolute working out of one’s life in the face of such inevitable finality. For the later Heidegger, the finite horizon of a particular epochal disclosure gifts Being to thought and determines it thereby. Authenticity in this case consists of giving oneself over to be appropriated by an event of Being. In contrast, Lonergan understands authenticity as being true to that primordial love which beckons us to intellectual probity and responsibility in working out life’s possibilities. This essay will illustrate how Lonergan’s analysis of the intentional structure of human conscious operations stands as a corrective to Heidegger’s early existential analysis of human being-in-the-world and later thought about Being. While Lonergan defines authenticity as loving openness to transcendent Being, Heidegger, because of his forgetfulness of the subject in her conscious operations, does not allow for a transcendence which stands beyond any finite horizon.